"The history of democracy in Latin America and the Caribbean, 1800-1870: an introduction". Issue 2 (3rd May 2020) - Posada-Carbó, Eduardo
ABSTRACT: This brief essay places the various articles of this dossier within the growing literature on the history of democracy, noting the neglect that Latin America and the Caribbean, in spite of some advances, continue to suffer in the field. It then highlights some of the contributions offered by the essays of the dossier.